2017
DOI: 10.1007/s12011-017-1072-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Cadmium, Chromium, Nickel, and Lead Ions Relays in Selected Polish Medicinal Plants and Their Infusion

Abstract: Concentration of Cd, Cr, Ni, and Pb were determined in peppermint leaves (Folium Menthae piperitae), chamomile blossom (Anthodium Chamomillae), and their infusions by atomic absorption spectrometry (AAS) after microwave digestion of plants samples. Peppermint and chamomile preparations by five different producers were purchased at various pharmacies in Poland. Infusions were made from herbs according to prescription for patients, provided by the producer of medicine on the package. Results show that in exam of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 13 publications
1
13
0
3
Order By: Relevance
“…The results obtained in this study, concerning lead contamination of samples of herbs and spices, correspond with earlier studies on this subject matter, conducted in Poland. Mirosławski and Pakuszto [ 26 ] analysed herbs (leaf of peppermint and flower of camomile) available on the Polish market and noted average levels of lead in the range of 0.440 mg/kg–1.110 mg/kg. Similar results concerning the levels of Pb in selected Polish herbs and spices (green matter of basil, root of curcuma, flower buds of clove tree, fruits of black pepper and peppers, onion, bear’s garlic, and allspice) were obtained by Krejpcio et al [ 27 ], who reported that the average content of lead varied in the range from 0.250 mg/kg to 1.490 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained in this study, concerning lead contamination of samples of herbs and spices, correspond with earlier studies on this subject matter, conducted in Poland. Mirosławski and Pakuszto [ 26 ] analysed herbs (leaf of peppermint and flower of camomile) available on the Polish market and noted average levels of lead in the range of 0.440 mg/kg–1.110 mg/kg. Similar results concerning the levels of Pb in selected Polish herbs and spices (green matter of basil, root of curcuma, flower buds of clove tree, fruits of black pepper and peppers, onion, bear’s garlic, and allspice) were obtained by Krejpcio et al [ 27 ], who reported that the average content of lead varied in the range from 0.250 mg/kg to 1.490 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Максимальные значения (0,72 мг/кг) зафиксированы для травы зверобоя и травы фиалки (Violae herba). Полученные результаты хорошо согласуются с российскими и иностранными данными литературы, согласно которым содержание кадмия в препаратах на основе индивидуальных растений редко превышает значение 0,8 мг/кг [21][22][23][24][25][26].…”
Section: Fig 2 Content Of Cadmium In the Herbal Medicinal Products unclassified
“…Herbs and plants have been popularly used as oral medicine in many countries around the world because of their low cost and effectiveness (Dghaim et al, 2015;. Several studies have examined that toxic metals such as cadmium (Cd), arsenic (As) and lead (Pb), could be present in some herbs (Chizzola et al, 2003;Filipiak-Szok et al, 2015;Mirosławski & Paukszto, 2018;Queralt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%